THE IMPLEMENTATION OF THE QUR'ANIC LEARNING PROGRAM IN THE PERSPECTIVE OF PARENT AND TEACHER AT THE PUBLIC ELEMENTARY SCHOOL TEMBOKREJO 2 PASURUAN INDONESIA - Ahmad Muhaimin; Aries Musnandar (Khatulistiwa, 2023)
This article delineates the implementation of the Qur’anic learning in elementary school from parent and teacher perspectives. The study discusses the importance of the teacher and parent role of in learning the Qur’an, especially on how to teach Quran properly. This research aims to find a positive contribution from the role of parents and teachers in improving students’ Quranic recitation process in school.Qualitative method is applied in this research, where data collection derived from interviews, field observations and through documentation studies. As the type of qualitative method, researcher presence in this study is a crucial moment in collecting and analyzing the data. The researcher analyzed it according to qualitative research procedures. The result of the study found that the role of teacher and parent in the realization of the success of a qualified learning activity is very important in order to improve students' learning achievement, increase worship practice (morning prayer). Showing role model by a teacher leads the students to higher achievement results in learning the Qur’an, it is not only being able to read the Qur’an quickly and accurately, but also eventually it can build the students’ noble character by conducting habitual actions. The writer concludes the manuscript with several propositions as the Quranic Learning Program can be effective if the school can involve parents in evaluating the program. Furthermore, the teacher should show exemplary good behavior such as respect, as well as to keep helping students whenever they need. Eventually, this program builds the student’s good behaviors.